Serological biomarkers predict immune-related adverse events and clinical benefit in patients with advanced gastrointestinal cancers - Wang, Yanni; Zou, Jianling; Li, Yun; Jiao, Xi; Wang, Yujiao; Zhuo, Na; Gao, Mengting; Gong, Jifang; Li, Jian; Zhang, Xiaotian; Wang, Xicheng; Peng, Zhi; et al. (Frontiers in Immunology, 2022)
Background Immune checkpoint inhibitors (ICIs) have dramatically improved survival in advanced gastrointestinal (GI) cancer patients, but also resulted in immune-related adverse events (irAEs). This study aimed to evaluate serological biomarkers of irAEs and treatment response in GI cancer patients. Patients and methods Metastatic GI cancer patients were enrolled between August 1, 2015, and July 31, 2017. Serum samples were collected at baseline, and a panel of 59 serum biomarkers was tested. The occurrence of irAEs was analyzed, and serological biomarker expression was correlated with irAE incidence and prognosis. Results Fifty-one patients were enrolled, of whom 47.1% (24/51) were diagnosed with irAEs, including 4 patients (7.8%) with grade 3-5 irAEs. The most common irAE was thyroiditis (9/51, 17.6%), followed by colitis (7/51, 13.7%). The expression of CD28 (P = 0.042), IL-4 (P = 0.033), IL-15 (P = 0.024) and PD-L1 (P = 0.018) was significantly elevated in patients with grade 3-5 irAEs. For organ-specific irAEs, IL-6 levels were higher in patients with thyroiditis and colitis, while IL-22 and SCF levels were higher in patients with colitis. Increased IL-1α, IL-21, LIF, and PIGF-1 levels were significantly associated with myositis incidence, while the serum levels of six cytokines (BTLA, GM-CSF, IL-4, PD-1, PD-L1 and TIM-3) were higher in patients with rash. Prognostic analysis showed that patients with irAEs had better tumor response (P = 0.029), improved PFS (median survival: undefined vs. 2.1 months, P = 0.002), and extended OS (median survival: undefined vs. 4.3 months, P = 0.003). The prognostic value of irAEs was only significant in patients who received anti-PD-1 inhibitors, but not in those who received anti-PD-L1 inhibitors. Besides, elevated BTLA (median OS: not reached vs. 7 months; P = 0.0168) and PD-1 (median OS: not reached vs. 7 months; P = 0.0223) concentrations were associated with longer OS. Conclusions Serological proteins are promising markers for predicting immune-related toxicity and prognosis in GI cancer patients. Organ-specific irAEs have various cytokine profiles. Although further validation is needed before clinical application, this study provided a direction for identifying patients at risk for irAEs, and guiding patient selection for ICI therapy.